The status of ECCD Centers in the rural areas the case of Culaba, Biliran - Borja, Paul Erick C.; Cañete, Pol Albert Trapal (Tacloban City Paul Erick Borja, 2011)
Various studies have shown that early childhood care and development (ECCD) programs create long-term impacts on children. The magnitude of the impacts however, varies on the quality of the program administered. This is dependent on the provider and the institutions that adminster such programs.
Since a majority of the institutions in the country that provide ECCD programs (the Barangay Day Care Centers) are public, the quality of programs they administer lies on how the Local Government Units (LGUs) extend support towards them. There are various ways of interpreting the quality of a center. This study explored the quality of the ECCD Centers of Culaba, Biliran in terms of its facilities, learning, and instructional materials.
Based on the results, the centers had not met the standards set by the Department Social Welfare and Development considering that they are underfunded by the LGUs. The centers rely heavily on the Barangay Government in meeting their needs to keep them operational. According to the day care workers, the reason for the low quality of programs delivered is due to the lack of budget among the Barangay Governments. They are hesitant to ask for funding in behalf of the parents since most of them belong to the lower socio-economic bracket. There is the need for LGUs and the government to reconsider investing in early childhood care considering that its positive impacts last longer compared to investing on the later stages in an individual's life.
The findings of this study is important because they can be used to provide an explanation for low cohort survival rates in the educational system and the inability of the students to maintain schooling until the end of the secondary level. It also guides the LGUs in policy making particularly in the provision of basic social welfare services.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science